Geochemical results of short sediment cores #18017, #18023, #201308, #20001, #20004, #20007 from the Baltic Sea - Kay-Christian Emeis; Ulrich Struck (PANGAEA, 2022)
Short sediment cores (multicorer) from Baltic Sea sediments in Arkona, Bornholm, Gdansk, and Gotland Basins were dated by 210Pb (constant rate of supply model) and were analysed for concentrations of inorganic and organic carbon, total nitrogen, aluminum and phosphorus. Sub-samples were analysed in a Heraeus Elemental Analyser for concentrations of total carbon and total nitrogen. Carbonate carbon has been quantified by using an Eltra CS Analyser that measures CO2 liberated by acidification with 2 N HCl; organic carbon was calculated as the difference between total and carbonate carbon. Total phosphorus and aluminum analyses were performed on the <63 micron sieved grain size fractions by ICP-OES. We find evidence for significant increases in the ratios of C to P in sediments younger than 15–25 years in cores from the Eastern Gotland basin, coincident with H2S build-up in deep waters. Paired oxygen and phosphorus concentration data from the sub-halocline water column of the Gotland Basin covering the time since 1970 suggest that phosphate diffuses out of the sediment under anaerobic conditions in deep water and adds to the dissolved phosphate pool. Our data imply that the sediment contributed approximately 14,000 t a^-1 of phosphorus to the water column of the deep Gotland Basin since the early 1970 extquotesingles.